Difficulties associated with Reporting Radiographer working practices – A narrative evidence synthesis. Issue 4 (November 2022) - Murphy, L.; Nightingale, J.; Calder, P.
Abstract: Objectives: This narrative synthesis of evidence identifies and explores issues that impact upon the expansion or effectiveness of Reporting Radiographers working in all diagnostic modalities within the United Kingdom (UK). The publication focuses on working practices affecting trainees and qualified Reporting Radiographers. Key findings: Fourteen studies informed the themes of this article, they were published between 2014 and 2021. Delays to commencement of reporting roles and variance in performance monitoring was common. Lack of formalisation, overly restrictive and out of date scopes of practice were also found. Whilst, staffing shortages contributed to underutilisation. Failure to utilise skills was most prevalent in cross sectional imaging modalities. Considerable variance in practice was also found between centres. Meanwhile, Reporting Radiographer involvement in professional development, education and research is far from universal and often dependant on individuals sacrificing their own time. Conclusion: Governance in many centres would benefit from renewal and standardisation, particularly relating to scopes of practice and performance monitoring audits. Measures are also required to encourage compliance with guidance, address staffing issues and reduce variation between centres. Failure to address these issues has the potential to impair collaboration, delay patient care and increase economic inefficiencies whilst negatively impacting satisfaction for service users and staff. Lack of involvement in professional development, education and research suggests Reporting Radiographers are not accomplishing their full potential, educating the next generation of the reporting workforce and driving evidence-based change for further development of the specialism. Implications for practice: Better use of the existing workforce is essential to increase productivity, value, and security of Reporting Radiographer services, which are essential to improve patient outcomes and efficiency.